2010
DOI: 10.1021/jp101658b
|View full text |Cite
|
Sign up to set email alerts
|

A Numerical Spectroscopic Investigation on the Functionality of Molecular Excitons in Tuning the Plasmonic Splitting Observed in Core/Shell Hybrid Nanostructures

Abstract: Coupling between localized surface plasmon resonance (LSPR) of metal nanoparticles and molecular excitons in core/shell hybrid nanostructures attracts increasing attention. Emphasis has been on fine-tuning exciton-plasmon coupling by controlling the LSPR of metal nanoparticles, while functionality of the intact excitonic resonance in this fine-tuning has received less attention. Our assertion has been that as a localized polarized excitation, just like the LSPR, the excitonic resonance should also sense the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…As a result, the optical responses of both the molecules and metal nanocrystal are strongly modified, leading to distinct spectral changes on the hybrid nanostructure in comparison to the spectra of the separate constituents. Due to the great importance of plasmonic–molecular resonance coupling in both the fundamental understanding of light–matter interactions and practical technological applications, a large number of experimental and theoretical studies have been devoted to it. On the basis of these studies, many applications have been demonstrated, such as biological sensing , and imaging, , infrared detection, and all-optical switches .…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the optical responses of both the molecules and metal nanocrystal are strongly modified, leading to distinct spectral changes on the hybrid nanostructure in comparison to the spectra of the separate constituents. Due to the great importance of plasmonic–molecular resonance coupling in both the fundamental understanding of light–matter interactions and practical technological applications, a large number of experimental and theoretical studies have been devoted to it. On the basis of these studies, many applications have been demonstrated, such as biological sensing , and imaging, , infrared detection, and all-optical switches .…”
Section: Introductionmentioning
confidence: 99%
“…1 Hybridization between plasmonic and molecular resonances can give rise to a variety of distinct optical properties which depend on the surface density and assembly behaviour of the dye adsorbed on the nanoparticle surface, the relative spectral overlap of both constituents as well as the distance between the dye layer and nanoparticle surface. A number of experimental [2][3][4][5][6][7][8][9][10][11] and theoretical [12][13][14] investigations have been recently reported characterising hybrid dye-metal nanoparticle structures. Of particular interest is the development of nanoparticle-enhanced spectroscopies including surface-enhanced Raman spectroscopy (SERS), 15 resonance energy transfer, 16 plasmon-enhanced fluorescence 17 and fluorescence quenching.…”
Section: Introductionmentioning
confidence: 99%
“…Even more, for an optimized shell thickness and oscillator strength, the excitonic resonance has been shown to experience an effective band splitting induced by dielectric medium. This was confirmed by a series of numerical experiments carried out to investigate effective medium effects on the absorption of core–shell hybrid complexes …”
Section: The Geometries and Morphologies Of Plasmon–exciton Nanostrucmentioning
confidence: 60%
“…It should be noted that not only the depth or width of the dip is extremely sensitive to the changes in the environment, but the excitonic resonance itself should also sense the effective dielectric medium provided by the metal core and the embedding medium . Even more, for an optimized shell thickness and oscillator strength, the excitonic resonance has been shown to experience an effective band splitting induced by dielectric medium.…”
Section: The Geometries and Morphologies Of Plasmon–exciton Nanostrucmentioning
confidence: 99%